Multiferroic BaCoX2O7 (X = P, As) Compounds with Incommensurate Structural Waves but Collinear Spin Ingredients. Issue 1 (9th November 2020) - Leclercq, Bastien; Arévalo‐López, Angel M.; Kabbour, Houria; Daviero‐Minaud, Sylvie; Pautrat, Alain; Basu, Tathamay; Colin, Claire V.; Das, Ranjana‐Rani; David, Rénald; Mentré, Olivier
Abstract: A new paradigm in multiferroics is observed in BaCoX2 O7 (X = As, P) compounds. They consist of one dimensional (1D) antiferromagnetic chains undulated by incommensurate structural modulations with unusually large atomic displacive waves, giving a mixed 1D/2D "real" magnetic topology. The magnetic ground state is antiferromagnetic (AFM) with k = [½ 0 0], leading to a nonmodulated collinear spin lattice despite the aperiodic atomic framework, and allows developing spin‐induced multiferroicity below T N . Severe arguments against the identified mechanisms for type‐II multiferroics, i.e., by inverse Dzyaloshinskii–Moriya, exchange striction and spin‐dependent p–d hybridizations, suggest an original scenario in which the atomic waves, the collinear magnetic structure, and magnetic dipole–dipole interactions may interact as crucial ingredients of the spin‐induced ferroelectric phase. Here, the specific role of the Co 2+ spin–orbit coupling in the magnetoelectric (ME) phase diagram is demonstrated by comparison with the novel Heisenberg BaFeP2 O7 isomorph, similarly structurally modulated. This compound shows a noncollinear modulated AFM ordering, while no ME coupling is detected in its case. Accordingly, both BaCoX2 O7 and BaFeP2 O7 also undergo metamagnetic transitions above 5–6 T promoted by the modulated distribution of spin exchanges, but the spin‐ flop progressive alignment of the spins in the noncollinear spin structure (Fe 2+ case) turns into an abrupt flip ‐like transition in the uniaxial spin structure (Co 2+ case). Abstract : BaCo(P, As)2 O7 is shown to be a type‐II multiferroics based on an original scenario in which incommensurate atomic shifts and collinear antiferromagnetic (AFM) Ising spins interact as crucial ingredients. In comparison no magnetoelectric coupling is detected in the Heisenberg BaFeP2 O7 isomorph, with strong spin‐lattice coupling leading to a modulated AFM spin structure. Magnetic dipole–dipole interactions are discriminating between them.